A surprise cell of origin for Barrett’s esophagus - von Holzen, Urs (Landes Bioscience, 2012)
Barrett’s esophagus is a metaplasia of the distal esophagus that is the only recognized precursor of esophageal adenocarcinoma. Despite a characteristic histology, the pathogenesis of Barrett’s has remained obscure. A recent paper from the laboratories of Wa Xian and Frank McKeon presents evidence for a novel cell of origin of Barrett’s. Their work is based on studies of mice engineered to lack the squamous epithelial stem cell survival factor p63. These mice develop a metaplasia of the proximal stomach and esophagus that harbors substantial histological and molecular features of Barrett’s. The metaplasia appears to form from embryonic progenitor cells that normally persists post-natally only at the squamo-columnar junction. Moreover, in their model, the metaplasia is initiated not by mutation but by reduced competition between these cells and squamous epithelial cells.